In vivo monitoring of the inflammatory response in a stented mouse aorta model - Kapnisis, Konstantinos; Pitsillides, Costas; Prokopi, Marianna; Lapathitis, George; Karaiskos, Christos; Eleftheriou, Polyvios; Brott, Brigitta C.; Anderson, Peter G.; Lemons, Jack E.; Anayiotos, Andreas (My University, 2016)
The popularity of vascular stents continues to increase for a variety of applications, including coronary, lower limb, renal, carotid, and neurovascular disorders. However, their clinical effectiveness is hindered by numerous postdeployment complications, which may stimulate inflammatory and fibrotic reactions. The purpose of this study was to evaluate the vessel inflammatory response via in vivo imaging in a mouse stent implantation model. Corroded and noncorroded self-expanding miniature nitinol stents were implanted in mice abdominal aortas, and novel in vivo imaging techniques were used to assess trafficking and accumulation of fluorescent donor monocytes as well as cellular proliferation at the implantation site. Monocytes were quantitatively tracked in vivo and found to rapidly clear from circulation within hours after injection. Differences were found between the test groups with respect to the numbers of recruited monocytes and the intensity of the resulting fluorescent signal. Image analysis also revealed a subtle increase in matrix metalloproteinase activity in corroded compared with the normal stented aortas. In conclusion, this study has been successful in developing a murine stent inflammation model and applying novel in vivo imaging tools and methods to monitor the complex biological processes of the host vascular wall response.
Keywords: In vivo imaging; Inflammation; Mouse stent model; Stent corrosion